The Use of Data Analytics Techniques to Assess the Functioning of a Government's Financial Management Information System : An Application to Pakistan and Cambodia - Hashim, Ali; Piatti-Funfkirchen, Moritz; Cole, Winston; Naqvi, Ammar; Minallah, Akmal; Prathna, Maun; So, Sokbunthoeun (World Bank, Washington, DC, 2019)
Public financial management enables government to implement policy. Financial management information systems are a central element of PFM in that they facilitate government financial transactions and subject them to rigorous budgetary controls. Therefore, the adequate use of FMIS systems supports the implementation of fiscal rules and provides the basis for holding the executive accountable for implementing the budget. Yet, the integrity of expenditure transactions and effectiveness of budget controls is rarely assessed. This paper explores the meaning of adequate use of FMIS systems and points to data analytics techniques that can shed light on how the use FMIS systems affects expenditure data integrity and effectiveness of budget controls. This methodology is applied to Pakistan and Cambodia, which reveals two very different problems. In Pakistan the analysis of the transactions profile suggests that a large share of the budget is not subjected to FMIS internal controls. In Cambodia the majority of the budget is channeled through the system, but the method exposes very large advances to commercial bank accounts that are subsequently drawn upon but outside the system. Both of these raise concerns about the effectiveness of the FMIS system. Deploying data analytics techniques can help assess whether FMIS systems serve form or function. Judging a system by its use is informative about governments' revealed preferences in expenditure management. This paper puts the spotlight on the foundation of expenditure data and advocates for a transparent, methodical and evidenced based approach to FMIS deployment and expenditure management reform.